2005
DOI: 10.1002/jbm.a.30466
|View full text |Cite
|
Sign up to set email alerts
|

Functional activity of insulinoma cells (INS‐1E) and pancreatic islets cultured in agarose cryogel sponges

Abstract: Here, we describe the preparation, structure, and properties of cryogel sponges, which represent a new type of macroporous biomaterial for tissue engineering. Cryogels were produced through freeze-thawing techniques, either from agarose alone or from agarose with grafted gelatin. The aim of this study was to evaluate agarose cryogel sponges as scaffolds for culturing both isolated pancreatic islets and insulinoma cells (INS-1E). In order to evaluate the effect of cell entrapment in artificial scaffolds, cell f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 26 publications
(31 reference statements)
0
42
0
Order By: Relevance
“…In this study, we showed how some of these factors can influence the properties and morphology of ABCGs. In addition, the data of our previous work, 7 as well as the results of ABCG biotesting carried out in this study, offer the promise of potential applications of these supermacroporous matrices as biocompatible 3D scaffolds for cell culture. A. V. Kaznacheev (A. N. Nesmeyanov Institute of Organoelement Compounds, Russian Academy of Sciences) for help with the microscopy experiments.…”
Section: 55mentioning
confidence: 81%
“…In this study, we showed how some of these factors can influence the properties and morphology of ABCGs. In addition, the data of our previous work, 7 as well as the results of ABCG biotesting carried out in this study, offer the promise of potential applications of these supermacroporous matrices as biocompatible 3D scaffolds for cell culture. A. V. Kaznacheev (A. N. Nesmeyanov Institute of Organoelement Compounds, Russian Academy of Sciences) for help with the microscopy experiments.…”
Section: 55mentioning
confidence: 81%
“…In the There were reports of growing islets for 49 days on chitoson sponge, 29 and 2 weeks on agarose cryogel. 30 So the behavior of mouse islets on gelatin/PVP scaffolds were determined in vitro. The direct contact assay showed that the cells were viable on all the scaffolds up to 48 h. In order to view the in growth of cells towards interior portion of the scaffolds, z sectioning was done present scenario, it is expected that the presence of PVP is an added benefit for maintaining structure and function of islet cells.…”
Section: Resultsmentioning
confidence: 99%
“…Their main applications are found in biocatalysis with immobilized cells [12,27,54,64,65] and enzymes [38,57,58], in bioseparations for purification of targets from particulatecontaining fluids [18, 30 -33, 37, 66, 67], chromatography of cell organelles [35], viruses [68], microbial [28,61,62], and mammalian [16,19,40] cells and in biomedical applications as 3-D matrixes for culture of mammalian cells [41,69].…”
Section: Applications Of Mgsmentioning
confidence: 99%